Variations of Electricity Supply Patterns in the Regions of Sumenep Madura Island - Eni Sri Rahayuningsih; Agus Suman; David Kaluge (Wacana Journal of Social and Humanity Studies, 2018)
The problem of limited electricity supplies in the Sumenep Madura Islands serves the background of this paper. This study aims to reveal the phenomenon of variations in the electricity supply patterns in Sumenep Madura Islands region. While employing rationality theory, social capital, and collective action, this present study used qualitative research methods with triangulation and snowball sampling techniques to bring out the truth of Emic. This study found that, while most of the geographical conditions of the Sumenep Islands were difficult to reach by transportation and communication facilities, this situation limited electricity supplies and caused a variety of electricity supply patterns. There were at least 6 patterns, each pattern had different characteristics: group size, relationship between group members, electricity use capacity per household (Watt), payment system (pre-paid or post-paid), usage time (hours/days), rates (IDR/household /month), potential conflicts, moral hazard potential, sustainability, perpetrators, and location. The author concludes that local community wisdom can be used as an effective and efficient solution to independently meet electricity demands in the areas whose resources are very limited. The results of this study can be used as a reference to solve problems in other locations that share similar characteristics.